Tax Aggressiveness Factors: The Role of Corporate Social Responsibility as a Moderation Variable - Suhendar, Dadang; Nurfatimah, Siti Nuke; Indrawan, Rizki; Mawardiana, Doni (SEIKO : Journal of Management & Business, 2024)
This study empirically investigates the effect of corporate social responsibility as a moderation variable on the effect of leverage, company size, and inventory intensity on tax aggressiveness in food and beverage sub-sector manufacturing companies in Indonesia. Secondary data collected from the annual reports of 22 companies listed on the Indonesia Stock Exchange (IDX), from 2018 to 2020, were used as panel data for the research sample of this study and regression analysis was applied to the proposed research model. The results of this study describe that leverage and inventory intensity have a positive influence on tax aggressiveness as measured by the ETR ratio. However, the strength of the effect of company size and inventory intensity on tax aggressiveness depends on the influence of corporate social responsibility as a moderation variable. The larger the CSR is proven to weaken the effect of company size and inventory intensity on tax aggressiveness, while the smaller the CSR is proven to strengthen the effect of company size and inventory intensity on tax aggressiveness. Moreover, CSR is unable to weaken the relationship between leverage and tax aggressiveness. Thus, CSR can be considered as recognition of legitimacy from external parties. In the end, this study contributes to the limited study of corporate governance on tax aggressiveness factors, by outlining the indirect influence of CSR on the effect of company size, leverage, and inventory intensity on tax aggressiveness in manufacturing companies in developing countries in Indonesia Keywords: tax aggressiveness, corporate social responsibility, inventory intensity, leverage and company size.